The Emergence of a New Security Apparatus in Greece: The Securitization of the Refugee/Covid-19 Crisis Nexus - Georgia Dimari (Coordinamento SIBA, 2021)
The aim of this article is to illustrate the securitization processes of the Covid-19 in Greece and the impetus they gave for the anew securitization of migrants and refugees. It is argued that their connectedness became feasible through their discursive presentation as a 'double crisis'. The central argument of this article is that two sub-components of the securitization of Covid-19 were also securitized, individuals and individual responsibility. The article hence posits the argument that these processes resulted in a quadruple securitization. More specifically, the discourse analysis conducted in speech acts of government and scientific actors reveals that migration and the refugee issue, Covid-19, individuals and individual responsibility are successfully securitized as there are all these elements articulated by the Copenhagen School – existential threats, securitizing actors, referent objects, emergency measures and audience acceptance – that make the securitization of each above issue successful. What is introduced and supported here, then, is that these securitization processes prompted the emergence of a new security apparatus in Greece.